The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13116074
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Black Soldier Fly Larvae Meal as Substitute of Fishmeal in Diets for Layer Chicks and Growers

Abstract: The acceptance of eco-friendly black soldier fly larvae meal (BSFLM) as sustainable alternative protein ingredient in poultry feeds continues to gain momentum worldwide. This study evaluates the impact of BSFLM in layer chick and grower diets on the growth, carcass quality and economic returns. Mean weekly weight gain and total live weight per chick and grower varied significantly. The highest final weight gain was achieved when birds were provided diet with 25.6% BSFLM. Average daily feed intake (ADFI), avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…Understanding the modulation of the gut microbial community by factors such as diet is very crucial as an essential component to chicken health 20,30 . Black soldier fly larvae (BSFL) meal is a promising and sustainable alternative to the expensive fishmeal in Layer chicken feed and a study done by 26 confirms that replacing fishmeal www.nature.com/scientificreports/ with BSFL does not comprise the overall growth and economic performance of the Layer chicken. This study aimed to analyze the effects of feeding black soldier fly (BSF) meal on the gut microbial composition of layer pullets using Oxford Nanopore 16S sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the modulation of the gut microbial community by factors such as diet is very crucial as an essential component to chicken health 20,30 . Black soldier fly larvae (BSFL) meal is a promising and sustainable alternative to the expensive fishmeal in Layer chicken feed and a study done by 26 confirms that replacing fishmeal www.nature.com/scientificreports/ with BSFL does not comprise the overall growth and economic performance of the Layer chicken. This study aimed to analyze the effects of feeding black soldier fly (BSF) meal on the gut microbial composition of layer pullets using Oxford Nanopore 16S sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Feed composition of the formulated diets fed to chicks for a period of eight (8) weeks 26 . Super layer premix contents per 2.5 kg: Vit.…”
mentioning
confidence: 99%
“…Similar results were reported by Anankware et al (2018) in broilers by feeding BSFLM. On the other hand, Pieterse et al (2018) reported no significant difference for commercial cutup parts and Sumbule et al (2021) reported no significant difference for breast yield and drumsticks yield and significantly (p<0.05) higher yield of thighs and wings.…”
Section: Resultsmentioning
confidence: 88%
“…Feed offered to the birds and unconsumed portions were weighed daily using a digital platform weighing scale (XK3190-A12, >300 kg, Gromy Scale Co., Ltd., Hangzhou, China) to calculate the average daily feed intake (ADFI). Total body weight gain and feed consumed were used to calculate the feed conversion ratio (FCR) for each dietary treatment according to the method described by Sumbule et al (34).…”
Section: Experimental Feed Formulationmentioning
confidence: 99%